CAPACITY BUILDING TRAINING FOR POKDARWIS GROUP IN NGESTIREJO TOURISM VILLAGE - TRISTANTI; YUDAN HERMAWAN; ADIN ARIYANTI DEWI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2022)
This capacity building training aims to increase ability and motivation as well as equip Pokdarwis groups to develop tourist villages in the Ngestirejo area. This training activity begins with needs analysis, planning, implementation, evaluation, and mentoring. The program target of this activity is the Pokdarwis Asmadewi group in the tourist village of Ngestirejo, totaling 25 people. The methods used include: lectures, discussions, and practice. The results of this activity are: (1) 25 people from the Asmadewi Pokdarwis group have been trained who are able to make tourism village development plans. (2) the Asmadewi Pokdarwis group is able to make an action plan which will later be implemented in the development of the Ngestirejo tourist village